2014
DOI: 10.5051/jpis.2014.44.1.2
|View full text |Cite
|
Sign up to set email alerts
|

How to improve the survival rate of implants after radiotherapy for head and neck cancer?

Abstract: Implants have been widely used in restorative treatment for patients who have undergone head and neck cancer surgery. With the development of combination treatment of head and neck cancer, radiotherapy has been a common means of therapy. However, it could induce various changes in hard and soft tissues and reduce the success and survival rate of the implants. Some research, using either animal models or clinical studies, have shown that certain strategies could be used for improving the survival rate of implan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 54 publications
1
14
0
2
Order By: Relevance
“…Our results indicate that implant survival is strongly influenced by radiotherapy, confirming previous findings [ 16 ] demonstrating that radiotherapy is an important factor in implant failure. Ihde et al [ 17 ] report that implant failure is a more significant risk (up to 12 times greater) in irradiated bone rather than in non-irradiated bone.…”
Section: Discussionsupporting
confidence: 91%
“…Our results indicate that implant survival is strongly influenced by radiotherapy, confirming previous findings [ 16 ] demonstrating that radiotherapy is an important factor in implant failure. Ihde et al [ 17 ] report that implant failure is a more significant risk (up to 12 times greater) in irradiated bone rather than in non-irradiated bone.…”
Section: Discussionsupporting
confidence: 91%
“…106 Radiotherapy, which is performed in 60-80% of the patients affected by head and neck cancer, 107 reduces cellular and vascular growth and therefore may significantly impair osseointegration of dental implants and increase the risk of complications (for example, osteoradionecrosis). 108,109 Both animal and human studies have shown an increased risk of implant failure (up to 12 times) in irradiated patients. 110 In a recent systematic review, Chambrone et al 111 reported a mean implant survival rate ranging from 46.3 to 98% and an increased implant failure risk (RR 2.74) in irradiated patients, in particular in the maxilla (RR 5.96).…”
Section: Head and Neck Cancer Patientsmentioning
confidence: 99%
“…Radiotherapy seems to have both early and late effects; the early effects affect mainly salivary glands, skin and oral mucosa, while the late effects involve bone changes and may lead to demineralisation, fibrosis, increased susceptibility to infection and avascular necrosis. 109 Several studies reported that hyperbaric oxygen therapy (HBOT) could significantly increase implant success and reduce unpleasant complications like osteoradionecrosis. 107,[112][113][114] However, two recent systematic reviews found that there is no evidence that HBOT can reduce implant failure and that better designed studies are needed to clarify the real benefit of HBOT on the survival rates of implants in irradiated jaws.…”
Section: Head and Neck Cancer Patientsmentioning
confidence: 99%
“…There is conflicting retrospective literature, which debates the use of hyperbaric oxygen (HBO) in treating host bone, specifically during craniofacial reconstruction after head and neck cancer. Some studies show improved vascularity and increased basic fibroblast growth factor of grafted recipient bone, 16 and other studies exhibit no significant difference in graft take with HBO. 17 Macroscopically, there is reliance on mechanical design of threaded implants to give the implant mechanical integration.…”
Section: The Recipient Sitementioning
confidence: 99%